Kualitas hidup orang tua yang memiliki anak Down Syndrome berdasarkan konsep Family Quality of Life (FQOL) - Rahmawati, Seliana Dwi (Literal: Disability Studies Journal, 2024)
This research is motivated by parents who have children with Down syndrome and have a low quality of life. The aim of this study is to understand the objective conditions of parents based on nine aspects of family quality of life. The research approach used is qualitative. The subjects of this study are three pairs of parents with children who have Down syndrome attending a special school (SLB) in Bandung City, aged between 35-45 years. The researcher collected data through observation, interviews, and document studies. The analysis conducted in this study involved data reduction, data display, and data verification. To ensure data validity, source triangulation was used. The results of this study indicate differences in conditions between fathers and mothers who have children with Down syndrome, where fathers do not experience much stress because they believe that the primary caregiving role falls to mothers. However, the stressors include increased financial needs and concerns about their child's future. In contrast, mothers experience a relatively high level of stress due to their child's limited abilities, which creates difficulties for them, including challenges in accessing appropriate healthcare services for their child. This research can serve as a foundation for future studies aimed at developing programs for parents with children with Down syndrome.